Sample Size Determination for Survey Research and Non-Probability Sampling Techniques: A Review and Set of Recommendations - Rahman, Md. Mizanur (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
If the researchers cannot collect data from a sufficient number of respondents using an appropriate sampling technique, it will be challenging for them to meet the study's primary objective. So, it is crucial for researchers to collect data from a large enough sample size and choose a suitable sampling method. Because there are so many different sampling strategies, and they come in such a wide range of forms, researchers need to have a solid understanding of how these techniques differ to select the method that will work best for their particular study. In this paper, the researcher addresses those crucial issues by setting two essential questions: a. what are the various non-probability sampling techniques? b. what the minimum possible number of participants required for survey research is? Non-probability sampling techniques have been discussed with the necessary example so that the readers can easily understand which method will be more appropriate for their study. In addition, some guidelines concerning the determination of appropriate sample size (sample size calculation using G* power, the sample size for categorical and continuous variables, sample to items, sample to variables, the sample size of CB-SEM, PLS-SEM) for survey research have been discussed in this study. This study will help researchers choose the non-probability sampling method(s) and minimum sample size to conduct their studies efficiently and fruitfully. Research paper Keywords: Sampling, non-probability sampling, sample size, survey research Reference to this paper should be made as follows: Rahman, M. M. (2023). Sample Size Determination for Survey Research and Non-Probability Sampling Techniques: A Review and Set of Recommendations. Journal of Entrepreneurship, Business and Economics , 11 (1), 42–62.